The roles of forest resources on the socioeconomic s of peripheral communities - Abdullah, Mukrimah; Mamat, Mohd Parid (2018)
Forest provides a wide variety of social and economic benefits. Globally, it is estimated that over 2.4 billion people depend on forest goods and services for the food, fresh water, medicines, employment and cash income. Forest also provides ecotourism services which also able to generate income of people.These benefits made forests become fundamental to the livelihoods and well-being of people, not only for the people who live in them, but also for those living in peripheral landscapes.A socio-economic study was undertaken among peripheral communities in the Northern Region of Peninsula Malaysia; Perak, Kedah and Perlis. The present paper intends to assess the socio-economic impacts of forest resources on the livelihood of surrounding communities using data and information collected through rapid rural appraisal (RRA), focus group discussion and household survey guided by structured questionnaire. A total of 1,052 households were successfully interviewed.The study found the average monthly income per household of these communities was RM1,672, RM2,138 and RM2,278 for Perlis, Perak and Kedah respectively. Meanwhile, the percentage of dependency on forest resources as a source of income was 5.3% to 13.3% from the total income.If there is no income from forest resources the poverty level of these communities may increase up to 5%. From the findings, forest conservation strategies should pay more attention to balance the needs for conservation and socio-economic livelihood of forest peripheral communities especially at Northern Region of Peninsula Malaysia.For example, the development of ecotourism areas near peripheral communities has potential to create local business and job opportunities. Promotion of communities based ecotourism (CBE) can be created as alternative ways to increase income thus improve the livelihood of the communities.